Do social influences, awareness, or experience matter? Toward a better understanding of Farm-related Injury Risk Perception among agricultural science college students in Ireland - Mohammadrezaei, Mohammad; Meredith, David; McNamara, John; Kinsella, James; Flannery, Sinéad (Frontiers in Public Health, 2023)
Introduction: Formal farm safety education/training should be tailored, in terms of the approach, content and delivery, to students undertaking agriculture education and training to enhance Farm-related Injury Risk Perception (FIRP). To this end, this paper identifies key factors including social influences, i.e. social confirmation/pressure to conform to cultural and behavioral norms exerted by ‘important others’ and peers, awareness, and experience affecting students’ FIRP. Methods: A cross-sectional online survey was conducted with a nationally representative sample of Bachelor of Agriculture Science (BAgrSc) students (N = 417) (aged 18-20) in Ireland. Descriptive (frequency and cross-tabulations) and inferential (Ordinal Logistic Regression (OLR)) analyses were applied to evaluate the effects of social influences, experience (of farming, of a near-miss or injury), and awareness (of others who were injured/killed on the farm) on FIRP. Results: The study found that social influences negatively affected FIRP. A relatively small number of students reported experiencing an injury (n = 56, 13.4%) that resulted in them being unable to participate in educational or social activities. A quarter of the respondents did, however, record experiencing a near-miss/close call (n = 106, 25.4%). A notable proportion (n = 144, 34.5%) of students had personal connections to someone who died as a consequence of a farm-related incident and 56.4% (n = 235) knew someone who was moderately/ severely injured. OLR findings established that experiencing a severe injury, having a near-miss or close call, and awareness of a farm-related death/injury positively affects FIRP. Conclusions: Perception of farm risks amongst students in Ireland is low. Students who recorded higher levels of risk perception were more likely to report experiencing a near-miss, close call or severe injury, or knowing someone who experienced a farm-related injury or fatality. Farmers, family or friends were found to negatively impact the FIRP and this reflects previous research findings. These findings highlight the need for education and training programs to enhance opportunities for student peer-to-peer learning through sharing of experiences and/or knowledge of farm injuries and/or fatalities. Such activities will enhance awareness and understanding amongst the general population of students leading to increased FIRP and a reduction in risk-taking.